Energy management of storage batteries based on forecasted PV output for small-scale standalone system - Mohd Shah, Ahmad Syahiman
In standalone photovoltaic (PV) system integrated with storage system, it is essential to have a load forecasting in order to fulfil demand of consumer. This project, will not do system sizing like conventional systems have but it will use specified battery capacity and manage the capacity efficiently, instead. The main task is to design a standalone system with small storage system that is capable to use this limited storage efficiently and smartly especially during unstable weather condition so that it can supply the energy when it is needed most by the consumer. This experiment proposes an energy management system based on next day forecast of generation in order to perform load scheduling beforehand so that a flow of stored energy in the batteries can be smooth. The system design contains a PV panel, 12V 40Ah lead-acid battery as storage device, MPPT charge controller and an inverter to convert the DC source of PV panel so it can be used by AC load.